Promoting critical thinking through debates about the internal conflict in Colombia in the EFL classroom with 9th graders (2020)
Events of recent Colombian history deserve the attention of all disciplines. The purpose of the study reported here is to understand how debates may promote critical thinking in a class of ninth graders of Bogotá. In the diagnosis stage, a lack of knowledge of the Colombian conflict was identified. With a participatory action research and collecting data by means of interviews, questionnaires and transcriptions of the debates we recorded the progress learners made in acquisition of information, reflection, analysis and structuring of arguments. In the pedagogical intervention we used four selected readings and four videos originally written in the English language. The contents and its discussion did not only inform, but also support language development. This internship expects to fill some of the gaps of knowledge that mark the learners’ understanding of their context, their behaviors, and axiological schemes.